PECULIARITIES OF PORCINE PERIODONTIUM IN NORMAL CONDITION AND IN GENERALIZED PERIODONTITIS DURING DENTAL RESTORATION OF VARIOUS TYPES - Popovych, І.Yu.; Petrushanko, Т.О.; Yeroshenko, G.А. (World of Medicine and Biology, 2020)
The paper was aimed at determining the structural features of porcine gums in normal conditions and experimental generalized periodontitis in the presence of adhesive bridges and dental implants. It is established, that impaired differentiation in the form of dyskeratosis occurs in the epithelium of the gingival mucosa of pigs with generalized periodontitis; it is manifested by the appearance of basal cells in the cytograms that are absent in the control group of animals, and 4-fold increase in the number of parabasal epitheliocytes. Histological study of the mucous membrane of the epithelial plate revealed vacuolar dystrophy of the cells in the spinous layer and local phenomena of spongiosis. In their lamina propria, disorders of microcirculation and connective tissue edema were noted. Changes in the lamina propria during dental restoration of different types were common. In the epithelium, during restoration with dental implant, the changes corresponded to the control group: vacuole dystrophy and local spongiosis. Marked hyperkeratosis in the epithelial plate was noted in restoration with bridge denture.
Keywords: experimental generalized periodontitis; adhesive bridge-like structures; dental implants; cytograms; gums; pigs